Pulsão e instinto: um diálogo entre a psicanálise e a biologia do comportamento - Mouammar, Christiane Carrijo Eckhardt (2010)
The current paperwork intends to analyze the concept of drive in both first and second theories of drives according to the Freudian psychoanalysis and refers to the behavioral biology in order to initiate a debate about the Trieb concept between these two areas of knowledge. According to Sigmund Freud, the concept of drive is the most important one and also the most obscure for the metapsychology. The complications regarding the meaning of this concept begin with translation problems and with divergences among several schools of psychoanalysis, which postulate different comprehensions referring to the word Trieb and Instinkt and referring to the way Freud used them in his texts to talk about the development of the psychic apparatus and its place in the construction of metapsychology. The view on the Instinkt drive being a totally inherited and automatic behavior is a misunderstanding for the own scientists in the area of behavioral biology. Freud uses in his texts the concepts of Trieb and Instinkt in turns and this research tries to elucidate if there was the need of this distinction and, thus, an emphasis is given on the definitions that Freud has postulated about the nature of both, sexual drive and death drive. Besides, the beginning of a dialogue between these Freudian concepts and the sexual drive and the drive of aggressiveness in the sociobiology of Edward O. Wilson and in the behavioral biology of Konrad Lorenz is carried out.